Numerical study of the photoelectron cloud in KEKB Low Energy Ring with a three-dimensional particle in cell method - L. F. Wang; H. Fukuma; K. Ohmi; S. Kurokawa; K. Oide; F. Zimmermann (Physical Review Special Topics. Accelerators and Beams, 2002)
A three-dimensional particle in cell simulation code has been developed to study the photoelectron cloud instabilities in KEKB LER. In this report, the program is described in detail. In particular, typical simulation results are presented for the photoelectron motion in various kinds of magnetic fields. The simulation shows that a solenoid is very effective in confining the photoelectrons to the vicinity of the vacuum chamber wall and in creating a region free of photoelectrons at the vacuum pipe center. The more uniform the solenoid field is, the more effectively does it suppress the electron-cloud buildup. Multipacting can occur both in a drift region and in a dipole magnet, and the heat load deposited on the chamber wall due to the lost electrons is important in these two cases. Electron trapping by the beam field as well as by various magnetic fields is an important phenomenon, especially inside quadrupole and sextupole magnets. Our numerical results qualitatively agree with the experimental studies.